Народна культура і побут закарпатців на сторінках періодичних видань краю другої половини XIX - поч. XX ст. - Федака, П. (Народна творчість та етнографія, 2007)
The author gives specific features of national culture and way of life of Transcarpathia residents. These very specific features were mentioned in periodicals.